1997
DOI: 10.1007/s002890050039
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of low-density polyethylene/polystyrene blends by segmented EB(PS-block-EB) n block copolymers

Abstract: Summary Hydrogenatedsegmented poly [butadiene-block-(styrene-block-butadiene)n] block copolymers, which were developed by use of a polymeric iniferter technique, were tested on their compatibilizing effectiveness for (10/90) LDPE/PS blends. They were found to be effective compatibilizers for this mixture, already giving a pronounced improvement in both tensile strength and strain of the blend at block copolymer concentrations of one percent. A concentration of five weight percent of segmented block copolymer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
0
15
0
2
Order By: Relevance
“…In earlier articles, 16,18 we published surprisingly good results with styrene (S)-butadiene (B) pentablock copolymers in the compatibilization of PS/ polypropylene (PP) blends. Kroeze et al 21 found hydrogenated segmented poly[B-block-(S-block-B)n] multiblock copolymers to be effective compatibilizers for low-density polyethylene/PS blends.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In earlier articles, 16,18 we published surprisingly good results with styrene (S)-butadiene (B) pentablock copolymers in the compatibilization of PS/ polypropylene (PP) blends. Kroeze et al 21 found hydrogenated segmented poly[B-block-(S-block-B)n] multiblock copolymers to be effective compatibilizers for low-density polyethylene/PS blends.…”
Section: Introductionmentioning
confidence: 98%
“…Two procedures are usually utilized in compatibilization: (1) use of functionalized polymers or reactive compatibilizers to form chemical bonds between the blend components and (2) addition of a block copolymer (BC) or a graft copolymer, the blocks of which have the same or similar chemical composition as the homopolymers in a blend of immiscible polymers. Although reactive compatibilization is now widespread, [1][2][3][4][5][6] BCs or grafted copolymers are still the most suitable compatibilizers [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the compatibilization of polyolefin/polystyrene (PS) blends.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary theoretical [1][2][3][4][5][6] and experimental [7][8][9][10] efforts are continually directed at enriching the current understanding of block copolymer phase behavior and dynamics under a wide variety of conditions. The ultimate objective of such efforts is to produce microstructured polymeric materials with the tailored properties needed to develop new, 11,12 as well as improve existing, 13 applications. Addition of a solvent to a microphase-ordered block copolymer affords a viable route by which to probe the order-disorder transition of highly segregated copolymers, 14 but is seldom employed 15 in morphological studies of ordered block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Sifat akhir bahan polipaduan yang dihasilkan sangat bergantung pada karakteristik polimer pengisi, meliputi konsentrasi dan jenis, dan sifat adesi antar muka matrik-pengisi yang menentukan kompaktibilitas polipaduan serta tingkat penyebaran polimer pengisi dalam matrik. Sejauh ini telah dilakukan beberapa penelitian bahan polipaduan yang mengkaji sifat mekanik [1][2][3], sifat kompaktibilitas polipaduan [4], sifat termal [1,5,6].…”
Section: Pendahuluanunclassified
“…Untuk mengetahui pengaruh pemberian bahan anti oksidan irganok 1076 terhadap struktur kristal bahan polipaduan yang mengalami perlakuan penjemuran di alam terbuka (di bawah sinar matahari) dapat diketahui dengan menghitung nilai derajat kristalinitas dari difraktogram bahan polipaduan PP-KA dan PP-KAIrganok 1076 8%. Hasil penghitungan derajat kristalinitas dari kedua polipaduan dengan metode standart dalam ditunjukkan pada Tabel 1.blends), sedangkan PVC-ABS termasuk polipaduan jenis kompak (miscible blends) [2,4]. Dalam penelitian yang mengkaji sifat tarik dari polipaduan telah dilakukan eksperimen pengukuran kebergantungan tegangan luluh, kekuatan tarik dan regangan patah serta modulus elastik pada konsentrasi bahan pengisi.…”
Section: Pendahuluanunclassified